Viśāle jagavistāre : Amerikāpravāsanuṃ varṇana - Paṭela, Maṇilāla Haridāsa, 1950- (Amadāvāda : Ḍivāina Pablikeśansa, 2015)
Travel narrative of United States.
In Gujarati.
Keywords: United States -- Description and travel; Paṭela, Maṇilāla Haridāsa, -- 1950- -- Travel -- United States; Paṭela, Maṇilāla Haridāsa, -- 1950-; Travel; United States